Point of care diagnosis of bovine trypanosomosis, tick-borne diseases and helminthoses with emphasis on portable anaemia-detection devices and decision support systems. - Magona, J.W. (University of Glasgow, 2004)
Effective diagnosis of major endemic bovine diseases such as trypanosomosis, tick-borne diseases and helminthoses that constrain agricultural production in sub-Saharan Africa is required for their rational treatment. However, this is hampered by the shortage of professional staff and unavailability of simple field-level diagnostic tests. The work presented in this thesis was designed to evaluate simple diagnostic tools and develop guiding decision support tools to facilitate diagnosis and treatment of these diseases in rural areas of Africa. Portable haemoglobinometers such as the Haemoglobin Colour Scale (HCS), HemoCue (HCU) and DHT -haemoglobinometer (DHT), commonly used in human medicine, were evaluated for their suitability in the detection of anaemia in cattle. Coefficients of variation (CY) were calculated for all methods to determine their precision over a range of 0-17 g/dl. The precision of the HCS (CV 2.9-8.8%) and HCU (CV 3.5-10.6%) was better than that of the DHT (CV 7.7-23%). There was good linearity between the readings of the HCS (R =: 0.925), HCU(R =: 0.920) and DHT (R =: 0.906) and those of the reference method (cyanmethaemoglobin). The diagnostic sensitivity and specificity of all methods for detection of anaemia (haemoglobin (Hb) < 8g1dl) was determined using the cyanmethaemoglobin method as a goldstandard. Sensitivity was defined as the ability of a method to detect true cases of anaemia (Hb < 8g1dl), while specificity was the ability of a method to declare the true non-anaemic status (Hb > 8 g/dl) as negative. The sensitivity ofthe HCS (94%) and HCU (80.5%) was high, but that of the DHT was low (52.7%). All the haemoglobinometers had high specificity: HCS (93%), HCU (96.5%) and DHT (100%). A high correlation between the packed cell volume (PCy) and Hb measurements was obtained using all methods: HCS (R =: 0.974), HCU (R =: 0.965) and DHT (R =: 0.934). Field veterinarians achieved good precision with the HCS (CV 8 - 13%) and the HCU (CV 1%). The cost of the kit and reagents for analysis of 1000 samples would amount to US$ 22 (? 19.50) for the HCS, US$ 600 (? 532) for the DHT and US$ 1100 (? 975) for the HCU, making the HCS cheapest to run. These haemoglobinometers are potentially useful for penside detection of anaemia, especially in rural areas of Africa. The influence of time of day and coat colour of Zebu cattle under tropical conditions on rectal temperature was assessed. The time of the day and coat colour had a highly significant influence on rectal temperature (P< 0.001) and thus need to be considered while assessing pyrexia during clinical diagnosis. The period between 13.00 and 17.00 hours was the most suitable time of the day for veterinarians to detect pyrexia, however there is the likelihood of picking healthy cattle (false positives) that have raised rectal temperature. Since veterinarians are usually presented with sick rather than healthy animals by farmers, it is unlikely that picking healthy animals would be a problem, Diurnal variations of the sensitivity of the common parasitological diagnostic tests for trypanosomosis were investigated. Despite the small sample size (n =: 2), the highest detection rate was observed at 21.00 hr and the lowest at 13.00 hr. Neither time of the day nor day-to-day variation had a significant influence on the sensitivity of the tests, despite occurrence of diurnal variations. Nevertheless, these results suggested optimal detection rate of trypanosomiasis with microscopy was achieved when cattle blood was taken and examined between 17.00 and 09.00 hours under tropical conditions. Epidemiological studies were conducted on endemic diseases in Zebu cattle kept under the mixed croplivestock production system in South East Uganda. Moderate parasitological prevalences of the diseases: anaplasmosis (23.6%), theileriosis (21.6%), fasciolosis (13.6%), Parasitic gastroenteritis (pGE) (6.7%), trypanosomosis (4.4%) and babesiosis (1.0%) were found. Morbidity rates